AN OVERVIEW OF THE EXPLOITATION OF STEAM IN THE SECONDARY SYSTEMS OF NPP KRŠKO - Novosel, Urška; Žvar, Matjaž; Ploj, Tomaž; Avsec, Jurij (Journal of Energy Technology, 2024)
Nuclear energy is used to produce electricity; it can also be applied in a cogeneration process to produce power and heat. Nuclear energy is a very clean source as it produces almost no greenhouse gases, such as CO2. Under the Kyoto Protocol, the signatory countries committed themselves to reducing CO2 emissions; therefore, it is reasonable to take advantage of existing nuclear facilities to the greatest extent possible. This means that even though they were built only to produce electricity (Krško NPP, for example), they can also be used for other applications: a source of heat for district heating or desalination of sea water in areas at risk of a lack of drinking water. Nevertheless, the technology can be upgraded by using the experience of other nuclear power plants (NPPs) having similar district-heating systems. In this paper, the focus was on models of steam consumption from the secondary system of the Krško NPP for the Krško and Brežice district-heating purposes. The Krško NPP has a Westinghouse PWR with 2,000 MWt and an electrical power output of 696 MW to the grid. The technological part is divided into three main systems: primary, secondary and tertiary. The first two are sealed and isolated from the environment while the third, which uses water from the River Sava for cooling, is connected to the outside environment. This paper focuses on the technical solution to obtain heat from the NPP’s secondary system for district-heating purposes. According to thermodynamic calculations, the secondary system determines the reduction of produced electricity, when the steam is exploited in front of the turbine. This paper presents some technical, economic and safety solutions for the highly efficient extraction of vapour for district heating. Furthermore, some thermodynamic calculations and technical solutions for district-heating purposes using the Krško NPP for the Krško-Brežice area are shown.